Profile of depigmenting cosmetics and dermatological products on the market - Priscila Aparecida Rotava; Juliana da Silva Favero; Keth Ribeiro Garcia; Valeria Weiss Angeli (São Paulo State University (UNESP), 2020)
The skin is the largest and most exposed organ of the human body, therefore subject to diseases and alteration of its appearance. Among these alterations, the cutaneous hyperchromia may be cited. Currently, the market offers numerous products with depigmenting action to the treatment of such disorders. The aim of this work was to analyze depigmenting products commercialized in establishments in the city of Bento Gonçalves (RS, Brazil) and websites of cosmetic companies. It was found 45 products with depigmenting action and, from these, 59 different active agents were identified. The main active compounds found were kojic acid, arbutin, ascorbic acid, hydroquinone and glycolic acid. Another observed data was that in 78% of the studied products the active substances were being used in combination. The most used vehicles were also studied as a reference to the use of sunscreen in the treatment of cutaneous hyperchromia. The present work had identified in the market a variety of products with depigmentation action and, because of this, it aims to serve as a reference to the healthcare professionals, especially at the prescribing moment, looking for the best results, with regards to treatment efficiency and safety.